A Redox‐Based Model for Carbonate Platform Drowning and Ocean Anoxic Events. Issue 13 (3rd July 2021) - Smith, B. P.; Kerans, C.; Fischer, W. W.
Abstract: The deposition of marine carbonate rocks is influenced by climate and seawater chemistry. Carbonate platforms usually keep pace with subsidence and sea level rise but "platform drowning" occurs when carbonate sedimentation slows or when siliciclastics replace carbonates. Identifying specific mechanism(s) behind platform drowning is critical for understanding global environmental changes such as Ocean Anoxic Events (OAEs). We developed a model for OAEs which couples ocean basin redox processes to rates of carbonate sedimentation. Well‐oxygenated oceans have steep gradients in saturation state such that deep‐ocean dissolution is balanced by carbonate "overproduction" in shallow water. Through anaerobic metabolisms, deep‐ocean anoxia reduces both dissolution and overproduction, leading to slower accumulation rates in shallow‐water environments. This quasi‐steady state response links carbonate sedimentation with longer timescales associated with redox changes. Redox‐based drowning may have acted alongside other mechanisms to create spatially diverse patterns of platform drowning during Mesozoic OAEs and other Phanerozoic hyperthermal events. Plain Language Summary: Carbonate minerals precipitate from ions dissolved in water. Thick packages of carbonate rocks often form in shallow, tropical waters, and their accumulation rate depends on the availability of ions as well as biological agents that catalyze carbonate deposition such as animals and microbes. Geologic patterns in carbonate rocks are sensitive to these controls on accumulation rates, tying them to Earth's surface chemistry and ecosystems. Sometimes chemical changes in the oceans cause far‐reaching effects that influence patterns observed in carbonate rocks. During the Mesozoic Era, episodes of lowered dissolved oxygen in the world's oceans often coincided with a phenomenon known as "platform drowning". Platform drowning occurs when carbonate platforms—sites of carbonate deposition like the modern Bahamian Islands—experienced slower sedimentation rates and sank into deeper water. Interestingly, there are several chemical pathways that could cause platform drowning, and unraveling the underlying drivers is key for understanding the nature of past environmental changes. Here we present a concept for platform drowning that emphasizes the role of microbes and their effects on global ocean chemistry. This idea helps explain the long timescales of platform drowning and may explain similar patterns during other low‐oxygen episodes in Earth's past. Key Points: A model for carbonate platform drowning was developed based on changing patterns of carbonate production and dissolution Ocean anoxia reduces both carbonate dissolution and the amount of carbonate "overproduction" in the surface oceans Linking carbonate chemistry to ocean redox conditions allowed slower sedimentation over long (10 5 –10 6 year) timescales